2012
DOI: 10.1002/iub.582
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical studies on glycation‐induced structural changes in human IgG

Abstract: Glycation of biomolecules leads to the formation of advanced glycation end products (AGEs). Glycation of immunoglobulin G (IgG) has been implicated in autoimmune diseases such as rheumatoid arthritis (RA). In this study, human IgG was glycated with physiological concentration of glucose. The changes induced in IgG were analyzed by UV, fluorescence, circular dichroism, and Fourier transform infrared (FTIR) spectroscopy; thermal denaturation studies, native, and Sodium dodecyl sulphate (SDS)‐polyacrylamide gel e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 33 publications
4
35
0
Order By: Relevance
“…Increasing concentrations of anti-AGE-IgG antibodies were incubated with a constant amount of antigen. Our previous study revealed fragmentation in AGE-IgG in SDS-PAGE (Ahmad et al, 2012). The same is visible here when antigen alone was electrophoresed (lane 1 ; Fig.…”
Section: Band Shift Assaysupporting
confidence: 83%
See 2 more Smart Citations
“…Increasing concentrations of anti-AGE-IgG antibodies were incubated with a constant amount of antigen. Our previous study revealed fragmentation in AGE-IgG in SDS-PAGE (Ahmad et al, 2012). The same is visible here when antigen alone was electrophoresed (lane 1 ; Fig.…”
Section: Band Shift Assaysupporting
confidence: 83%
“…In our previous study, we have shown that in vitro treatment of human IgG with glucose causes structural alterations in IgG (Ahmad et al, 2012). The glycation induced alterations in IgG were examined by UV spectroscopy which showed hyperchromicity at 278 nm as compared to native IgG, which may be attributed to the exposure of chromophoric aromatic amino acid residues due to the unfolding and fragmentation of protein as a result of glycation (Jairajpuri et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibitors were native IgG and AGE-IgG. iological concentration of glucose for 20 days exhibited extensive damage analyzed by various physicochemical techniques [19]. AGE-IgG was found to be a potent antigenic stimulus inducing high titre antibodies in rabbits as compared to native IgG [20].…”
Section: Discussionmentioning
confidence: 99%
“…Spermine and spermidine have been shown to display a significant antiglycation effect at physiological concentration suggesting the role for polyamines in diabetes [67]. Many of the secondary complications of diabetes result from protein glycation and oxidation mediated by agents and processes against which carnosine may protect [68,69]. Additionally there are a number of observations which suggest an inverse relationship between diabetes and carnosine.…”
Section: Introductionmentioning
confidence: 99%